Rapid and Low-Cost Culture-Based Method for Diagnosis of Mucormycosis Using a Mouse Model - Vaezi, Afsane; Fakhim, Hamed; Ilkit, Macit; Faeli, Leila; Fakhar, Mahdi; Alinejad, Vahid; Wiederhold, Nathan P.; Badali, Hamid (Frontiers in Microbiology, 2020)
Prompt and targeted antifungal treatment has a positive impact on the clinical outcome of mucormycosis; however, current diagnostic tools used in histopathology laboratories often fail to provide rapid results. Rapid culture-based strategies for early diagnosis of Mucorales infections, which may influence treatment decisions, are urgently needed. Herein, we evaluated a microculture assay for the early diagnosis of mucormycosis in an immunocompetent murine model of disseminated infection, by comparing it with traditional diagnostic methods. The assay specificity was assessed using blood (n = 90) and tissue (n = 90) specimens obtained from mice infected with Rhizopus arrhizus using different inoculum sizes (1  104, 1  105, and 1  106 colony forming units (CFUs)/mouse) and blood (n = 15) and tissue specimens (n = 15) from uninfected mice. Surprisingly, 26 of 90 (28.9%) blood samples revealed positive results by microculture, whereas all blood samples were negative when assayed by conventional culture. The overall positive conventional culture rate for the mouse tissue (kidney) samples was 31.1% (28/90). The calculated sensitivity for kidney microculture was 98.8% (95% confidence interval [CI] 96.6%–100%), with an assay specificity of 100%. Hence, the microculture assay may be useful for rapid culturing and diagnosis of mucormycosis caused by R. arrhizus directly in blood and tissue samples. Hence, this method may allow for the timely administration of an appropriate treatment. Keywords: microculture, rapid diagnosis, Rhizopus arrhizus, mucormycosis, murine model